2020
DOI: 10.1101/2020.08.30.273656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RetroCHMP3 Blocks Budding of Enveloped Viruses Without Blocking Cytokinesis

Abstract: SummaryMany enveloped viruses require the endosomal sorting complexes required for transport (ESCRT) pathway to exit infected cells. This highly conserved pathway mediates essential cellular membrane fission events and therefore has limited potential to acquire adaptive mutations to counteract this co-option by viruses. Here, we describe duplicated and truncated copies of the ESCRT-III factor CHMP3 that arose independently in New World monkeys and mice and that block ESCRT-dependent virus budding. When express… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 98 publications
4
15
0
Order By: Relevance
“…Therefore, in contrast to retroCHMP3 proteins in New World monkeys, which became less cytotoxic before acquiring activating stop codons, retroCHMP3 proteins in mice had substantially less time to sample mutations, even when accounting for the shorter generation times of mice compared to primates. Consistent with the relatively early acquisition of an activating stop codon, we previously found that mouse retroCHMP3 remains significantly more cytotoxic than squirrel monkey retroCHMP3 (Rheinemann et al, 2020), raising the question of how murine retroCHMP3, with the exception of the pseudogenized copy encoded by Mus minutoides (Fig. 5A), remained intact for millions of years.…”
Section: Expression Of Mouse Retrochmp3 May Be Controlled By Interferon Signalingsupporting
confidence: 58%
See 4 more Smart Citations
“…Therefore, in contrast to retroCHMP3 proteins in New World monkeys, which became less cytotoxic before acquiring activating stop codons, retroCHMP3 proteins in mice had substantially less time to sample mutations, even when accounting for the shorter generation times of mice compared to primates. Consistent with the relatively early acquisition of an activating stop codon, we previously found that mouse retroCHMP3 remains significantly more cytotoxic than squirrel monkey retroCHMP3 (Rheinemann et al, 2020), raising the question of how murine retroCHMP3, with the exception of the pseudogenized copy encoded by Mus minutoides (Fig. 5A), remained intact for millions of years.…”
Section: Expression Of Mouse Retrochmp3 May Be Controlled By Interferon Signalingsupporting
confidence: 58%
“…1b). These observations provide strong evidence that CHMP3 retrocopies is positively selected for antiviral activity against ESCRT-dependent enveloped viruses (Rheinemann et al, 2020). Due to the broad reliance of virus families on the ESCRT pathway, CHMP3 retrogenes could provide broad inhibitory activity against the budding of diverse virus classes.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations